Analysis of Characteristics, Bioeconomics, and Optimization of Sustainable Management of Largehead hairtail (Trichiurus Lepturus) Commodities in Coastal Waters of Pangandaran Regency - Kisam, Annisa Rahmawati; Yustiana, Yooce (School of Life Sciences and Technology, Institut Teknologi Bandung, 2025)
Largehead hairtail (Trichiurus lepturus) is a potential fish commodity in the seawaters of Pangandaran Regency. Fishing activities operate under an open-access regime, allowing unrestricted participation. The lack of catch restrictions can lead to overfishing. This research aims to determine the optimal level of production, fishing effort, and economic rent, both in terms of biology and economics, to ensure sustainable management of largehead hairtail resources in Pangandaran Regency. The research method used is a case study that includes both primary and secondary data. Primary data were collected through direct interviews with government officials, stakeholders, and fishermen, while secondary data, in the form of capture fisheries statistics for 2018–2023, were obtained from Cikidang Fishing Port. The analysis employs biotechnical analysis, bioeconomics, and static optimization using the Gordon-Schaefer model for bioeconomic analysis. The results showed that the standard fishing gear was purse seine with an average CPUE (catch per unit effort) of 32.86 kg/trip. Biological parameter estimation resulted in an intrinsic growth rate (r) of 0.872 tons per year, a fishing gear coefficient (q) of 0.00012 tons per trip, and an environmental carrying capacity (K) of 277,083 tons. Largehead hairtail resources in Pangandaran have not yet reached overfishing. The utilization rate of largehead hairtail was 42.69% with a ‘develop’ status. The Maximum Economic Yield (MEY) management regime provides the largest economic rent of Rp549,802,899 per year, with a maximum fishing effort of 3,684 trips per year and a maximum catch of 80.35 tons per year.